Degradation of Dichloromethane Containing Laboratory Wastewater Using Photoelectric Fenton Process - C. Rubi, Rugi Vicente; Cabiles, Daniel C.; C. Reyes, Raven Auriesh; V. Abiog, Reine Yvonne; Domingo, Maureen Ann; Evangelista, Albert D. C.; H. Lavilles, Francis Dominic (Journal of Sustainable Materials Processing and Management, 2023)
Conducting laboratory experiments in educational institutions has been linked with the increased amount of chemical waste disposed in the environment. The excessive usage and disposal of Dichloromethane (DCM) has been attributed to financial and environmental concerns. This present study aimed to treat the DCM containing laboratory wastewater using Photoelectric Fenton (PEF) process. The PEF treatment was done at varying ultraviolet (UV) light intensity (3, 6 and 9 Watts), sacrificial anode (Al, Cu and TiO2), and oxidizing agent (OA) loading ratio (1.13, 3.76, and 6.39 w/w) under 30oC and 1 atm. Results have shown that the highest degradation (99.82%) of DCM was obtained at 9 Watts of UV light intensity, 3.76 w/w [H2O2]:[Fe2+] OA loading ratio, and with TiO2 coated with IrO2 and RuO2 as the anode. It was detected that higher UV light intensity favors the degradation efficiency when using the TiO2 coated with IrO2 and RuO2 anode. On the other hand, higher OA loading ratios proved to negatively affect the process as high concentrations of H2O2 become ineffectual for the degradation of organics. Finally, analysis of variance (ANOVA) showed the positive correlation between degradation efficiency and UVA light intensity. This confirmed the applicability of the PEF process in degrading of recalcitrant pollutants in wastewater, thus showing potential for mitigating its environmental impact.